A systematic review and meta‐analysis of patient‐reported outcomes following nerve transfer surgery for brachial plexus injury. Issue 11 (1st April 2022) - Haldane, Chloe; Frost, Geoffrey; Ogalo, Emmanuel; Bristol, Sean; Doherty, Christopher; Berger, Michael
Abstract: Objective: The purpose of this systematic review and meta‐analysis was to determine the effect of nerve transfer surgery for brachial plexus injury (BPI) on patient‐reported outcomes. Literature Survey: MEDLINE, EMBASE, and CINAHL were searched and screened in duplicate for relevant studies on September 25, 2019 and repeated June 24, 2020. Methodology: The patient population included male and female patients who received nerve transfer surgery for BPI. Further inclusion criteria were: (1) all levels of evidence; (2) published in English; (3) conducted in humans; and (4) report of patient‐reported outcome. Two reviewers independently abstracted data regarding injury type, surgical technique, surgical timing, follow‐up duration, strength, and patient‐reported outcome measures. Quality was assessed in duplicate using the Methodological Index for Non‐Randomized Studies criteria. Synthesis: Twenty‐one studies involving 464 participants were included in analyses. The mean age ± SD was 32.4 ± 1.8 (range: 5–77) and 89.2% of included participants were male. The mean time to surgery was 5.6 ± 0.6 months and the mean follow‐up time was 48.1 ± 8.4 months. The most used patient‐reported outcome was the Disabilities of Arm, Shoulder and Hand (DASH), where scores variably improved postoperatively, although the degree of disability remained high. Return to work was reported in five studies, with 66.0% of participants returning to work. Patient satisfaction was assessed in four studies with an overall satisfaction proportion of 64.0%. Pain was assessed in 12 studies using various measures. In studies reporting pain intensity postoperatively, 29.3% of patients were "pain‐free" or had "no pain." Conclusions: Patient‐reported outcomes following nerve transfer for BPI are infrequently reported in the literature. Although patient‐reported outcomes demonstrate variable postoperative improvement, there is evidence of ongoing limitations and postoperative DASH scores report a high degree of ongoing disability. Future studies with greater reporting as well as validation of patient‐reported outcomes within BPI are warranted.